2015
DOI: 10.1242/dev.124248
|View full text |Cite
|
Sign up to set email alerts
|

Distinct developmental and genetic mechanisms underlie convergently evolved tooth gain in sticklebacks

Abstract: Teeth are a classic model system of organogenesis, as repeated and reciprocal epithelial and mesenchymal interactions pattern placode formation and outgrowth. Less is known about the developmental and genetic bases of tooth formation and replacement in polyphyodonts, which are vertebrates with continual tooth replacement. Here, we leverage natural variation in the threespine stickleback fish Gasterosteus aculeatus to investigate the genetic basis of tooth development and replacement. We find that two derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(108 citation statements)
references
References 88 publications
6
101
0
1
Order By: Relevance
“…Genetic mapping experiments have identified genomic regions underlying evolved phenotypes 46 , and in a few cases, the functional roles of specific candidate genes have been tested 7,8 . A number of genomic regions underlying morphological changes have been identified with promising candidate genes, but these candidates have not yet been functionally tested 912 . In addition, sticklebacks are common models for studies of population genetics/genomics 13,14 , speciation 15 , behavior 1 , endocrinology 16 , ecotoxicology 17 , immunology 18 and parasitology 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mapping experiments have identified genomic regions underlying evolved phenotypes 46 , and in a few cases, the functional roles of specific candidate genes have been tested 7,8 . A number of genomic regions underlying morphological changes have been identified with promising candidate genes, but these candidates have not yet been functionally tested 912 . In addition, sticklebacks are common models for studies of population genetics/genomics 13,14 , speciation 15 , behavior 1 , endocrinology 16 , ecotoxicology 17 , immunology 18 and parasitology 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, only one of the trans-eQTL hotspots n (continued) found in this study (Chr12a) overlapped with genomic regions repeatedly found to be associated with marine/freshwater divergence by Hohenlohe et al (2010), Jones et al (2012), or Terekhanova et al (2014. Nevertheless, several studies indicate that adaptation to novel aquatic environments may also involve parts of the genome outside these large target regions (DeFaveri et al 2011;Leinonen et al 2012;Ellis et al 2015;Erickson et al 2016;Ferchaud and Hansen 2016). The QTL underlying physiological adaptations to different aquatic environments in sticklebacks have not been well characterized.…”
Section: Discussionmentioning
confidence: 63%
“…Successful colonization of these diverse habitats necessitates behavioral, morphological, and physiological adaptation to novel environmental conditions including changed temperature, salinity, oxygen, light, parasite and predator regimens, a process that can occur rapidly (Kitano et al 2010;Barrett et al 2011;Terekhanova et al 2014;Lescak et al 2015;Huang et al 2016, Rennison et al 2016. Parallel adaptations between independently founded freshwater populations frequently involve the same regions of the genome and arise from preexisting genetic variation in the marine population (Colosimo et al 2005;Hohenlohe et al 2010;Jones et al 2012;Liu et al 2014;Conte et al 2015, but see DeFaveri et al 2011Leinonen et al 2012;Ellis et al 2015;Ferchaud and Hansen 2016). Local adaptation in environmentally heterogeneous habitats such as the Baltic Sea (Guo et al 2015) and lake-stream complexes (Roesti et al 2015) has been shown to involve the same genomic regions.…”
mentioning
confidence: 99%
“…In cichlids, lower pharyngeal jaw morphology varies dramatically 32,33 and has been shown to be adaptive and correlated with trophic niche 34 . Multiple freshwater stickleback populations have evolved dramatic increases in ventral pharyngeal tooth number 23,35,36 . Recent work has demonstrated that the developmental genetic basis of this evolved tooth gain is largely distinct in two independently derived populations of freshwater sticklebacks 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple freshwater stickleback populations have evolved dramatic increases in ventral pharyngeal tooth number 23,35,36 . Recent work has demonstrated that the developmental genetic basis of this evolved tooth gain is largely distinct in two independently derived populations of freshwater sticklebacks 36 . Unlike mammalian teeth, fish regenerate their teeth continuously throughout adult life 37 .…”
Section: Introductionmentioning
confidence: 99%